Kreativitas Bentuk Iringan Musik Pada Paduan Suara Muslimat Desa Bergas Kidul Di Semarang (Universitas Negeri Semarang, 2019)
Muslimat Choir is an art that combines two elements of music namely Choir and regional Musical Instruments (Angklung) and has its own technique in using Angklung as a Choir Accompaniment. Muslimat Choirs Become One of the Icon of Tourism Village in Bergas Kidul Village, Bergas District, Semarang Regency. The purpose of this study was to find out and describe the creativity of the Muslimat choir musical accompaniment in the Bergas Kidul village in Semarang. This study was examined using a qualitative musicology approach. Data collection techniques include interviews, observation, and documentation. The data analysis technique used is interactive analysis techniques which include data reduction, data presentation, and conclusion drawing. This study shows that the use of traditional Angklung musical instruments is to use the A Man method. the composition of the music on the songs contained in the Muslimat Choir, using the Angklung instrument, using Arabic and Indonesian verses using melodies that move to jump and step up and down including in close harmony, have medium and fast tempo variations tend to be dynamically loud using the signal 4/4. Advice that can be given by the author is that the music will be more colorful if the addition of rhythmic instruments such as drums, because the drum can also keep the tempo more suitable and the music becomes more festive.